MENANGKAL RASISME DI ERA DIGITAL - Nur Hadiyati; Renny Christiarini; Amanda Rosetia; Violina Anastasya; Tiara Sonita; Evita Kordinata; Habeebanisya Habeebanisya; Kelven Liong; Nurliana Dwi Putri; Ameilia Cantikasari; Sofia Lorence; Ricky Hartanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Racism is an attitude created by humans towards humans to create a degree of limitation among humans through culture, skin, or anything that they think is strange/different in their groups. In this article, we want to emphasize the people's awareness of racism that occurs starting from among young people. According to the Central Statistics Agency, in Indonesia alone there are 1340 ethnic groups in Indonesia. Because there are so many ethnic groups in Indonesia, Indonesia is called a plural state. The method used is qualitative, namely interviews and quantitative questionnaires because the writer needs to get resources from people who are experts in their fields and also need to know the situation about racism in the vicinity.